Avaliação do Microsoft Kinect v2 como instrumento de medição das oscilações posturais - Gonçalves Gonzalez, Diego Ramon (2017)
The measurement of body sway is employed in the assessment of postural control. However, many devices assigned to this function are bulky or require special preparation, such as attachment of markers. In this study, The Microsoft Kinect v2, which is a portable and markerless motion sensor, was used as an instrument to measure body sway. Fortysix volunteers had their trajectories of center of mass (CM) and center of pressure (CP) measured by a Kinect v2 and a force plate, respectively, during upright stance with eyes open or close, on stable or unstable surface (Airex foam). Discriminatory ability of the instruments between conditions was evaluated using parameters from CM and CP. The Spearman correlations between parameters from measurements of both instrument was also calculated. Sway area, range and RMS value from CM and CP presented high correlation ( > 0.7). Only the parameters based on the mean velocities discriminated between all four conditions, for both instruments. Although future studies must consider the limitations of the device, the present results suggest that Kinect v2 may be used as an instrument to measure body sway.